Isotopic trophic guild structure of a diverse subtropical South American fish community. Issue 1 (24th August 2012) - Burress, Edward D.; Duarte, Alejandro; Gangloff, Michael M.; Siefferman, Lynn
Abstract Characterization of food web structure may provide key insights into ecological function, community or population dynamics and evolutionary forces in aquatic ecosystems. We measured stable isotope ratios of 23 fish species from the Rio Cuareim, a fifth‐order tributary of the Rio Uruguay basin, a major drainage of subtropical South America. Our goals were to (i) describe the food web structure, (ii) compare trophic segregation at trophic guild and taxonomic scales and (iii) estimate the relative importance of basal resources supporting fish biomass. Although community‐level isotopic overlap was high, trophic guilds and taxonomic groups can be clearly differentiated using stable isotope ratios. Omnivore and herbivore guilds display a broader δ13C range than insectivore or piscivore guilds. The food chain consists of approximately three trophic levels, and most fishes are supported by algal carbon. Understanding food web structure may be important for future conservation programs in subtropical river systems by identifying top predators, taxa that may occupy unique trophic roles and taxa that directly engage basal resources.